Presentasjon av dr.avhandlinger - Åman, Sonja Irene; Colman-Denstad, Erica (Tidsskrift for kulturforskning, 2024)
Governing the People of the Whale, History and Politics of Aboriginal Subsistence Whaling av Sonja Irene ÅmanWildness and control: Mediating technology and perceptions of nature in nineteenth century Norway av Erica Colman-Denstad